Histomorphological Effects of Tadalafil on the Liver of Adult Wistar Rat - P. O. Onyilo; B. O. Samuel (Journal of Applied Sciences and Environmental Management, 2024)
Tadalafil is used to treat erectile dysfunction and improve exercise capacity in people with pulmonary arterial hypertension. It promotes blood circulation to the penis during sexual stimulation, thus facilitating the occurrence of an erection. This study examined tadalafil effects on the liver, focusing on potential hepatotoxicity and liver function adverse effects. It aims to contribute to knowledge on tadalafil misuse and abuse, promoting informed decision-making and raising awareness. The study was conducted using fifteen (15) adult Wistar rats randomly assigned into three groups consisting of 5 rats each. Group A was the control group while group B (10 mg/kg of tadalafil) and C (20 mg/kg of tadalafil) were the low dose and high dose groups respectively. Oral administration of tadalafil in treated rats showed evidence of vascular congestion and dilation in the liver tissue, at 20 mg/kg there was periportal hepatitis. Assay of liver function parameters showed increase in liver enzymes across treatment groups compared to control. The presence of periportal hepatitis indicates potential inflammation in the region surrounding the portal area of the liver which suggests that tadalafil may have an impact on hepatocyte morphology and may also influence the inflammatory response in the periportal region of the liver. Hence, Tadalafil should be taken with caution.